Environmental Training and Synaptic Functions in Young and Old Brain: A Presynaptic Perspective - Bonfiglio, Tommaso; Vergassola, Matteo; Olivero, Guendalina; Pittaluga, Anna (Current Medicinal Chemistry, 2019)
Background: Aging is an unavoidable, physiological process that reduces the complexity and the plasticity of the synaptic contacts in Central Nervous System (CNS), having profound implications for human well-being. The term “cognitive reserve” refers to central cellular adaptations that augment the resilience of human brain to damage and aging. The term “Cognitive training” indicates the cultural, social and physical stimulations proposed as add-on therapy for the cure of central neurological diseases. “Cognitive training” reinforces the “cognitive reserve” permitting to counteract brain impairments and rejuvenating synaptic complexity. The research has begun investigating the clinical impact of the “cognitive training” in aged people, but additional work is needed to definitively assess its effectiveness. In particular, there is a need to understand, from a preclinical point of view, whether “cognitive training” promotes compensatory effects or, alternatively, if it elicits genuine recovery of neuronal defects. Although the translation from rodent studies to the clinical situation could be difficult, the results from pre-clinical models are of high clinical relevance, since they should allow a better understanding of the effects of environmental interventions in aging-associated chronic derangements in mammals. Conclusion: Data in literature and the recent results obtained in our laboratory concerning the impact of environmental stimulation on the presynaptic release of noradrenaline, glutamate and gamma amino butyric acid (GABA) suggest that these neurotransmitters undergo different adaptations during aging and that they are differently tuned by “cognitive training”. The impact of “cognitive training” on neurotransmitter exocytosis might account for the cellular events involved in reinforcement of “cognitive reserve” in young and old animals.
Keywords: glutamate